1998
DOI: 10.1159/000040814
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic Events in Beta Thalassemia Major: An Italian Multicenter Study

Abstract: Thromboembolic (TE) events have been frequently reported in β-thalassemic patients in association with known risk factors such as diabetes, complex cardiopulmonary abnormalities, hypothyroidism, liver function anomalies, and postsplenectomy thrombocytosis. In a recent survey involving 9 Italian thalassemic centers, we identified 32 patients with TE episodes in a total of 735 subjects, of whom 683 had thalassemia major and 52 thalassemia intermedia, corresponding to 3.95 and 9.61%, respectively. There was a gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
132
2
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(142 citation statements)
references
References 14 publications
(14 reference statements)
5
132
2
3
Order By: Relevance
“…The incidence was 3.95% among 685 ␤-TM patients and 9.61% among 52 patients with ␤-TI. 7 The same group reported a lower incidence (1.1%) of thromboembolic complications among 1146 patients with ␤-TM who were followed for 37 years. 7 Another study showed a 5.3% overall incidence of thrombotic complications among 495 patients with thalassemia whose median age was 28 years.…”
Section: Deep Venous Thrombosis and Pulmonary Embolismmentioning
confidence: 93%
See 2 more Smart Citations
“…The incidence was 3.95% among 685 ␤-TM patients and 9.61% among 52 patients with ␤-TI. 7 The same group reported a lower incidence (1.1%) of thromboembolic complications among 1146 patients with ␤-TM who were followed for 37 years. 7 Another study showed a 5.3% overall incidence of thrombotic complications among 495 patients with thalassemia whose median age was 28 years.…”
Section: Deep Venous Thrombosis and Pulmonary Embolismmentioning
confidence: 93%
“…7 The same group reported a lower incidence (1.1%) of thromboembolic complications among 1146 patients with ␤-TM who were followed for 37 years. 7 Another study showed a 5.3% overall incidence of thrombotic complications among 495 patients with thalassemia whose median age was 28 years. 1,2 In this study, the prevalence of thromboembolic events was 3.3% among 421 patients with ␤-TM and 16.2% among 74 patients with ␤-TI, although 15.3% of these patients had predisposing congenital or acquired factors contributing to the hypercoagulability.…”
Section: Deep Venous Thrombosis and Pulmonary Embolismmentioning
confidence: 93%
See 1 more Smart Citation
“…Thromboembolic events were encountered in two large cohorts of thalassemia patients, including both thalassemia major and TI patients, with a frequency of 4.3% και and 5.2%, respectively. 38,39 It must be noted that the prevalence of such events was higher in splenectomized patients than in non-splenectomized ones. In particular, thromboembolic complications were even more frequent in transfusion-independent splenectomised TI patients (29%), compared to regularly transfused TM patients (2%).…”
Section: 37mentioning
confidence: 99%
“…[59][60][61] Clinically, the prevalence of thrombotic events in patients with β-thalassemia intermedia can reach up to 20%, compared to less than 1% in patients with β-thalassemia major. 30,[62][63][64] These events are mostly venous and primarily occur in splenectomized patients (22.5% vs. 3.5% prevalence rate in splenectomized vs. non-splenectomized patients; P<0.001). 30,64 Other risk factors for thrombotic events include advancing age, total hemoglobin level less than 9 g/dL, history of thrombotic or other vascular events, elevated platelet (>500x10 9 /L) and nucleated red blood cell counts (>300x10 6 /L), 30,43,64,65 while other conventional risk factors are often absent in such patients.…”
Section: 57mentioning
confidence: 99%